Do Macroeconomic Factors Influence Household Consumption Expenditure in the Gambia? ARDL-Error Correction Regression Approach - Jallow, Mamadou Salieu; Hamadou, Issa (The Eastasouth Journal of Social Science and Humanities, 2024)
Consumption constitutes a larger part of GDP and contributes immensely in enhancing economic growth and development of a country. This study examines the influence of macroeconomic factors on household consumption expenditure in the Gambia. To achieve our objective, we employ ARDL estimation method with Bounds tests to analyze our study using secondary times series data collected from World Bank’s World Development Indicators database from 2000 to 2020. The findings reveal that GDP, inflation, direct credit to private sector, remittances and population all have significant effect on household consumption expenditure in the short run because their p values are less than 0.05 at 5% level of significance. For the long run effect, the CointEq (-1)* is negative and statistically significant. It means that the short run is adjusted with high speed in the run approximatively 108%. Therefore, GDP, inflation, direct credit to private sector, inflation, remittances and population are all significantly affecting household consumption in the long run. Thus, the study recommends that Government of the Gambia to use a mix macroeconomic policy method to stimulate and increase household consumption expenditure in order to help in achieving economic growth and development. The study further recommends future researchers to include other macroeconomic variables like unemployment and interest rate.